Legitimation of University in Modern Culture - M. A. Vasilyeva; O. V. Bezzubova (Moscow Polytechnic University, 2022)
The authors propose to consider university as a significant cultural topos. The significance of the topos is provided by the narrative integrated in it. It reflects the values and inscribes the university into the current cultural situation. The authors give several historical examples to support their thesis that this narrative is a response to external cultural challenges. The current situation is rife with such challenges, and therefore, the creation of a legitimizing narrative for the university turns out to be quite problematic. The authors study the influence of such factors as massification of education, media communication, social, demographic changes, etc. Examples of modern Russian and foreign universities demonstrate self-legitimization process of the university and show its visual part. The universities represent their own position, history and current values by creating their own visual code. The authors adduce as examples modern universities' websites with the visual images that are presented on their title pages. Based on this material, the authors draw a conclusion about the main modern strategies of self-legitimation of the university as positioning on the scales: tradition and innovation, loyalty to the government and independence from it, history and community.